# Prove the absorption law in propositional logic [closed]

Can the absorption law, $p \vee (p \wedge q) \equiv p$, be proved using other laws in propositional logic?

## closed as off-topic by B. Goddard, Namaste, user91500, kingW3, ShaunSep 8 '17 at 17:51

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – B. Goddard, Namaste, user91500, kingW3, Shaun
If this question can be reworded to fit the rules in the help center, please edit the question.

Let $p,q \in S$.
$\begin{array}{l:l}\quad p\lor(p\land q) \\=(p\land \top)\lor(p\land q) & \top\text{ is the identity for }\land \\=p\land(\top\lor q)&\land \text{ distributes over }\lor \\ =p\land\top&\top\text{ is the annihilator for }\lor&\text{Identities of Boolean Operators are also Zeroes of their Dual} \\ =p&\top\text{ is the identity for }\land \end{array}$
The result: $p=p\lor (p\land q)$
By Dual Symmetry : $p=p\land (p\lor q)$